CompTIA A+ complete study guide - Docter, Quentin; Dulaney, Emmett A.; Skandier, Toby. (Indianapolis, Ind. : Wiley Pub., 2009)
"The essential study tool for the 2009 edition of the CompTIA A+ exam The CompTIA A+ certification is the industry standard in terms of measuring a technician's hardware and software knowledge. As the most popular entry-level certification, it is particularly popular among individuals switching from another career to computers. Organized by ojectives this unparalleld study guide offers you a systematic approach to preparing for the CompTIA A+ certification, and includes real-world scenarios, chapter review questions, plus a CD with Sybex's propriety test engine to reinforc all of the concepts you learn. Covers both the A+ Essentials (Exam 220-701) and IT Technician (Exam 220-702) CD featuring nearly 200 review quetsions, practice exams, flashcards, and the book in a searchable PDF Bestselling author Emmett Dulaney arms you with insight to the most up-to-date best practices that are the focus of the new exam"--Provided by publisher.
Personal computer system components -- Storage devices, power supplies, and adapters -- Understanding display devices -- Understanding laptops and portable devices -- Installing and configuring printers -- Operating system features and interfaces -- Installing and configuring operating systems -- Troubleshooting theory and preventive maintenance -- Troubleshooting operating systems, hardware, printers, and laptops -- Understanding networking -- Understnding network security fundamentals -- Understanding opeational procedures -- Installing, maintaining, and troubleshooting -- Installing, configuring, and troubleshooting laptops -- Resolving printer problems -- Operating system structures and commands -- Operating system utilities and troubleshooting issues -- Installing and troubleshooting networks -- System security.
"Covers exams 220-701 and 220-702"--P. [1] of cover.
Includes index.
System requirements: PC running Microsoft Windows 98, 2000, NT4 (with SP4 or later), Me, XP, or Vista; Internet connection; CD-ROM drive.
Keywords: Computing Technology Industry Association -- Examinations -- Study guides; Microcomputers -- Maintenance and repair -- Examinations -- Study guides; Operating systems (Computers) -- Examinations -- Study guides; Computer technicians -- Certification -- Study guides